Improved Thermoelectric Performance of Tellurium by Alloying with a Small Concentration of Selenium to Decrease Lattice Thermal Conductivity - Saparamadu, Udara; Li, Chunhua; He, Ran; Zhu, Hangtian; Ren, Zhensong; Mao, Jun; Song, Shaowei; Sun, Jingying; Chen, Shuo; Zhang, Qinyong; Nielsch, Kornelius; Broido, David; et al. (ACS Applied Materials and Interfaces, 2019)
Phonon scattering through alloying is a highly effective way to reduce lattice thermal conductivity due to the mass difference between the host and alloyed atoms and strains caused by the different atoms. In this work we investigate the thermoelectric properties of Te between 323 and 623 K. By varying the alloying concentration of Se, a minimum lattice thermal conductivity was achieved with ∼10% (by stoichiometry) alloying of Te by Se. Additionally, Sb has been used as a dopant to increase the carrier concentration of the system. With reduced lattice thermal conductivity by Se alloying and increased carrier concentration by Sb doping, the room-temperature figure of merit (ZT) increased by 60%, leading to an average ZT of ∼0.8 in Te 0.88 Se 0.10 Sb 0.02 , which corresponds to an engineering figure of merit (ZT) eng ∼ 0.5 between 323 and 623 K and an efficiency of ∼8% in the same temperature range. The results indicate that the combination of Se alloying and Sb doping is successful in improving the thermoelectric properties of Te.
CRIS-Team Scopus Importer:2022-04-14
Keywords: alloying; average ZT; ball milling; elemental Te; hot pressing; Te; thermoelectric